Vacuum assisted wound healing: can it prove to be cost- effective? - Samant, Saurabhi M.; Sarang, Bhakti (International Surgery Journal, 2018)
Background: In search for a faster and effective method Negative pressure wound therapy (NPWT) also known as Vacuum assisted wound closure (VAC) has emerged to be a promising technology over the years. This study was carried out to determine the clinical efficacy and cost effectiveness of Vacuum assisted closure (VAC) therapy compared to conventional wound therapy. Methods: A prospective randomised study using VAC was performed on cases with chronic non healing wounds using a low cost negative pressure therapy unit. The negative pressure used in the vacuum assisted closure of the wounds was provided by the wall mounted centralised suction apparatus which provided a constant average pressure of 125 mm of Hg (range being 110-200 mm Hg). Results: The rate of wound healing which was exhibited by reduction in size of the wound by more than 1 cm at the end of the first 5 days was higher in the cases (82%) as compared to the control (18%) group. By end of 15 days size reduction of >3 cm was seen almost 85% of the patients treated with NPWT. The total cost incurred in the first group undergoing VAC for a period of 15 days per patient was Rs.750 (11.16) as against the second group undergoing conventional wound dressing which was Rs.700 (10.41) for the same period per patient. The cost- benefit analysis of the two groups statistically revealed a p value of <0.05 under 95% confidence limits, thus proving vacuum assisted closure, though slightly expensive than the conventional dressing, to be a better and cost effective modality, taking into consideration the faster wound healing rates. Conclusions: In this study NPWT appeared to exhibit better wound healing and is thus a promising alternative to the conventional management and has a potential to be replicable across many hospitals with financial constraints in the low and middle income countries.